Analisis Teknis Dan Ekonomis Perbandingan Efektivitas Proses Marking Rambu Bending Lambung Kapal Secara Manual Dan Semi Automatis - Ardhi Razzaq Alviano; Minto Basuki (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
This study aims to analyze the effectiveness and the economic side of the process of manual or semi-automatic bending signs. The data required for both types of marking methods are data on the number of operators, company working hours, effective working hours, and the results of the production process. After that it is done by data processing, data processing in this study uses the Experimental Method, in the Manual marking process, the process is done by directly drawing on the multiplex material according to the drawing design using 2 operators, in the Semi Automatic marking process, the use of a CNC machine is done by using only 1 operator and also using a setting on a CNC machine of 50 Amperes. So from the data that has been managed later, it shows that the use of CNC machines as a substitute for manual marking has a positive effect on the company. Which can reduce the amount of operator usage, get more results from the Manual marking process, and use less electricity. So overall, the marking process using the Semi Automatic method is better from all sides compared to the marking process using the Manual method.